Plasmodium kentropyxi n.sp. (Apicomplexa: Haemosporina: Plasmodiidae) and a Plasmodium tropiduri-like parasite in the lizard Kentropyx calcarata (Lacertilia: Teiidae) in North Brazil - Lainson R.; Landau I.; Paperna I. (Parasite, 2001)
Plasmodium kentropyxi n.sp. is described in the teiid lizard Kentropyx calcarata from north Brazil. Young asexual stages and gametocytes are at first polar in the erythrocyte but with elongation, move to a lateral position. Largest meronts seen contained from 30-40 nuclei and conspicuous greenish-black pigment granules located in a distinct vacuole. With growth the gametocytes eventually assume a smooth, curved cylindrical shape, with evenly rounded ends. Pigment is scattered or concentrated around a conspicuous vacuole which is slowly developed as the gametocytes mature. Mature male parasites measured 11.8 x 4.0 μm (9.6 x 4.2 - 13.2 x 3.6 μm), shape-index 2.9 (2.2 - 5.0), and females 13.5 x 4.5 μm (12.0 x 4.5 - 15.0 x 4.8 μm), shape-index 3.0 (2.2 - 3.8). Some larger meronts may slightly enlarge the erythrocyte, but most asexual stages and the mature gametocytes rarely do so. A second, P. tropiduri-like parasite encountered in K. calcarata possessed small rounded or fan-shaped meronts producing from 4-14 merozoites, and spherical to subspherical gametocytes of approximately 6.0 x 5.0 μm. The parasite was consistently polar in its position in the erythrocyte.